Change in adipose tissue characteristics and lipid metabolism in natural grazing Mongolian cattle with age - Xueting Yu; Lu Chen; Xige He; Yunfei Han; Yajuan Huang; Rina Sha; Gerelt Borjigin (Animal Bioscience)
Objective This study aimed to elucidate the lipid composition, characteristics, and metabolic mechanisms of subcutaneous adipose tissue (SAT) in natural grazing Mongolian cattle during its development. Methods The experimental animals consisted of castrated Mongolian cattle, divided into two groups: 10 months old (10 M, n = 12, average weight: 113.26±0.87 kg) and 34 months old (34 M, n = 12, average weight: 390.44±1.23 kg). All animals were selected from the same herd in the Eren Nur grasslands, Xilingol, Inner Mongolia, China. Browning-related genes in SAT were determined using quantitative reverse transcription polymerase chain reaction with 3 replicates for each cattle, and six animals from each group were randomly selected for non-targeted lipidomic techniques to analyze the changes in lipid metabolism with 6 replicates. Results The yellowness value and relative expression of mitochondrial biogenesis-specific markers, thermogenic markers, uncoupling protein-2 (UCP2), and beige adipocyte marker genes in the SAT increased with age. Multivariate analysis revealed 172 significantly different lipids (SDLs). Triacylglycerols and phosphatidylcholines showed high relative contents. Glycerol and sterol lipid levels were predominantly upregulated during development, whereas phospholipids and sphingolipids were primarily upregulated at 10 M. Developmental time greatly influenced the fatty acid composition of neutral lipids, phospholipids, and free fatty acids. Pathway analysis demonstrated that the 172 SDLs were primarily involved in glycerophospholipid, glycerolipid, ether lipid, and sphingolipid metabolism. Conclusion The developmental stage significantly affected the lipid quantity, composition, and metabolism of SAT in Mongolian cattle. Certain functional lipids, such as medium-long-chain triglycerides, fatty acid ester of hydroxyl fatty acid, and vitamin D, were detected in the yellow fat of natural grazing Mongolian cattle. These findings provide a comprehensive reference for the metabolic characteristics of yellow fat in Mongolian cattle, contributing to the meat industry chain.